Modelling of Lower Hybrid Current Drive in the Tore Supra Tokamak - Nilsson, Emelie (My University, 2012)
In the Tore Supra tokamak, lower hybrid (LH) waves at a frequency of 3:7 GHz are coupled to the plasma for current drive using a Full Active Multijunction (FAM) launcher and/or a Passive Active Multijunction (PAM) launcher, which was installed recently to test an ITER-relevant antenna design. A number of discharges have been performed in Tore Supra, using either or both launchers, in a variety of plasma conditions including fully non-inductive scenarios. As a mediator between experimental measurements and current drive theory, simulations play an important role. In this work, a comparative modelling of non-inductive LH current drive with FAM and PAM launchers is presented. A suite of codes specifically coupled and optimized for LH current drive modelling is used, including a code for equilibrium and transport (METIS), LH coupling (ALOHA), LH wave propagation (C3PO), absorption (LUKE), and fast electron bremsstrahlung (FEB) emission reconstruction (R5X2). The modelling suite provides a calculation of the current profile, LH power deposition, and a synthetic diagnostic for the FEB emission of the LH accelerated electrons in the energy range 50 110 keV. The reconstructed emission can be directly compared to FEB measurement from hard x-ray (HXR) detection system. A study of fully non-inductive discharges with either the FAM or PAM launchers shows a good agreement between experiments and simulations for such discharges at relatively low density (n < 2 1019 m3). On Tore Supra, the FAM or PAM parallel refractive index spectra (nk) are found to be noticeably different. In particular, a secondary lobe located at a relatively low value of jnkj in the PAM has a negative contribution to the plasma current. Radial profiles of FEB emission in the energy range 60 80 keV have routinely been used in Tore Supra analysis. The work of this thesis shows that this profile is not a valid approximation, since the HXR detectors registers a strictly positive quantity, regardless of the direction of the emitting electrons. Thus, inverted HXR profiles can be used as a relative measurement of the current profile only in the absence of secondary lobes driving a significant current. Another conclusion is that FEB emission measurement is insufficient to compare experiments that used FAM or PAM launcher in similar plasma conditions since the FEB profiles may look similar while the driven current can be very different.
Keywords: Fysik; Physical Sciences